Development of a villi-like micropatterned porous membrane for intestinal magnesium and calcium uptake studies. (November 2019) - Gommers, Lisanne M.M.; Skrzypek, Katarzyna; Bolhuis-Versteeg, Lydia; Pinckaers, Nicole E.T.; Vrijhof, Rob; van der Wijst, Jenny; de Baaij, Jeroen H.F.; Stamatialis, Dimitrios; Hoenderop, Joost G.J.
Graphical abstract: Abstract: Intestinal enterocytes are key players in the absorption of magnesium (Mg 2+ ) and calcium (Ca 2+ ). Understanding the exact molecular mechanisms by which their absorption behavior is regulated could greatly improve treatment strategies for stimulating intestinal absorption in diseases with Mg 2+ and/or Ca 2+ deficiency. However, such studies are hampered by the lack of in vitro intestinal cell models mimicking the mechanical and physiological properties of the gut. In this study we develop an in vitro gut model based on porous micropatterned membranes with villi-like surface topography and mechanical properties closely mimicking that of intestinal tissue. These membranes are prepared via phase separation micromolding using poly-ε-caprolactone/poly-lactic-glycolic acid (PCL/PLGA) polymer blend and can facilitate cellular differentiation of Caco-2 cells similar to native enterocytes. In fact, cells cultured on these micropatterned membranes form a brush border of microvilli with spatial differences in morphology and tight junction formation along the villous-base axis. Moreover, cells cultured on our membranes show a 2-fold increased alkaline phosphatase activity at the end of differentiation. Finally, we demonstrate that cells cultured on our micropatterned membranes have a 4- and 1.5-fold increased uptake of 25 Mg and 45 Ca, respectively, compared to non-patterned membranes. These results indicate that the new membranes can mimic the intestinal environment and therefore can have a great impact on mineral uptake in vitro . Statement of Significance: This study presents the development of an in vitro gut model consisting of villi-like PCL/PLGA micropatterned membranes. These membranes are prepared via phase separation micromolding (PSμM), a technique which allows tailoring of the membrane surface topography combined with membrane porosity and interconnectivity which are important parameters for membranes used for in vitro transport studies. The culture of Caco-2 cells on these micropatterned membranes shows that they facilitate cellular differentiation similar to gut enterocytes. Our data indicate that mimicking the 3D geometry of the gut is very important for improving the physiological relevance of in vitro gut models. In the future, our micropatterned membranes with segment-specific geometries, in combination with isotopic measurements, would be applied to perform detailed ion uptake and transport studies.